Energy profile of repetition sprint exercises with different rest durations - Shiraki, S.; Ogata, M.; Yamamoto, K.; Kigoshi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2022)
he present study aimed to examine the profile of energy metabolism during repetition sprint exercises with different rest durations. Nine competitive male track and field athletes performed a submaximal-intensity increment exercise and 4 kinds of 2 consecutive 30-s sprints tests with rest durations of 4, 10, 15, and 20 min, respectively. The mean power output during these sprints was evaluated as the average value over the entire 30-s period. Aerobic and anaerobic energy during these sprints was determined from the extrapolated linear regression between power and the steady-state O2 uptake obtained during the submaximal-intensity increment exercise. During 2nd sprints compared with 1st sprints in the respective tests, the mean power output decreased significantly in the tests with rest durations of 4, 10, and 15 min; in all the tests, the aerobic energy increased significantly and the anaerobic energy decreased significantly. These results suggest that the 1st sprint in a repetition sprint exercise causes activation of aerobic metabolism and inhibition of anaerobic metabolism during the 2nd sprint. On the other hand, it is also suggested that recovery of anaerobic metabolism after the 1st sprint requires a longer rest duration than that for recovery of performance in the repetition sprint exercise.